Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s11032-015-0243-3
|View full text |Cite
|
Sign up to set email alerts
|

Waterlogging tolerance is associated with root porosity in barley (Hordeum vulgare L.)

Abstract: Tolerance to waterlogging is an important breeding objective for barley (Hordeum vulgare L.); however, it is a complex quantitative trait. It is difficult to screen large numbers of lines in the field due to environmental variability, and it is also challenging to screen large numbers in controlled conditions if yield data are to be collected. The direct measurement of traits that contribute to waterlogging tolerance, such as aerenchyma development in roots, may offer advantages especially if molecular markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 31 publications
4
50
3
Order By: Relevance
“…All the genotypes had a low percentage of root porosity and no significant differences were found among genotypes. Our results were slightly different from the report by Broughton et al (2015), who found not only higher percentage of root porosity but significant differences among barley genotypes when subjected to hydroponic aerated solutions. It is possible that the aerated hydroponic solution generated slight hypoxic conditions (or perhaps increased root ethylene), causing the increase of root porosity in waterlogging-tolerant genotypes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…All the genotypes had a low percentage of root porosity and no significant differences were found among genotypes. Our results were slightly different from the report by Broughton et al (2015), who found not only higher percentage of root porosity but significant differences among barley genotypes when subjected to hydroponic aerated solutions. It is possible that the aerated hydroponic solution generated slight hypoxic conditions (or perhaps increased root ethylene), causing the increase of root porosity in waterlogging-tolerant genotypes.…”
Section: Discussioncontrasting
confidence: 99%
“…After 21 days of waterlogging treatment, growth parameters, including longest adventitious root length, shoot dry weight, and root dry weight were reduced to 20-80 % of the same growth parameters in aerated conditions (Broughton et al 2015;Garthwaite et al 2003;Mcdonald et al 2001;Pang et al 2004). After 7 days of waterlogging treatment, the longest adventitious root length, shoot dry weight and root dry weight of all the six genotypes also decreased by 40-95 % of the same growth parameters in aerated conditions.…”
Section: Waterlogging Influence On Plants Growthmentioning
confidence: 96%
“…Identification of a QTL for root porosity (as a surrogate for aerenchyma) in barley (Broughton et al . ) is of interest to explore also for wheat. Moreover, microarray analyses of laser micro‐dissected root tissues of maize (Rajhi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Progress in research on root aeration in crops is worthwhile to highlight. Identification of a QTL for root porosity (as a surrogate for aerenchyma) in barley (Broughton et al 2015) is of interest to explore also for wheat. Moreover, microarray analyses of laser micro-dissected root tissues of maize (Rajhi et al 2011) and rice (Shiono et al 2015) have identified candidate genes for aerenchyma (maize) and ROL barrier induction (rice).…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic protective system is destroyed by oxidation caused by oxidative free radicals and the cell membrane is destroyed by lipid peroxidation, which leads to waveshaped epithelial cells, a few fragmented cells, destroyed pulp cavity to a different extent, and increased pore space to increase water-transporting capacity (Broughton et al, 2015). Therefore, the proportion between the pericycle and total root thickness is significantly increased and the degree of lignification deepened.…”
Section: Changes In the Contents Of Some Trace Mineral Elements And Vmentioning
confidence: 99%